Penerapan Strategi Pembelajaran Kooperatif Tipe Team-Assisted Individualization (TAI) untuk Meningkatkan Penguasaan Mufradat Siswa - Nurul Ramadhani; Saepudin; Raodhatul Jannah (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2024)
This research aims to determine the effectiveness of applying the Team-Assisted Individualization (TAI) cooperative learning strategy in improving the Arabic vocabulary mastery of eighth-grade students at MTs Nurul Ilmi Barukku in Sidenreng Rappang Regency. The study employs a quantitative approach with an experimental research type and a pre-experimental design in the form of pre-test and post-test. The research sample consists of 18 randomly selected students. The results show a significant improvement in students' vocabulary mastery after implementing the TAI strategy. The average pre-test score of 20.83 increased to 83.89 in the post-test. This indicates that the application of the TAI cooperative learning strategy is effective in enhancing students' Arabic vocabulary mastery, particularly related to الْمِهْنَةُ الطِبِّيَّة (medical professions). The study concludes that the TAI strategy can be a good alternative for Arabic vocabulary learning.